Ukrepi upravljanja z Naturo 2000 v slovenskem gozdarstvu - Kogovšek, Tadej (Gozdarski vestnik, 2011)
The authors present Slovenian experiences in the field of biodiversity sustaining in the forest area. Due to the long tradition of close-to-nature forest management and, consequently, well preserved forests, over 50% of sylvan space has been included into Natura 2000. Legislative changes in the field of forestry result from the transfer of European directives in Slovenian legal system. The new tasks require changes in forest management planning and cooperation of the institutions covering the fields of forest management and nature protection. Integration of Natura management in forest management plans is demonstrated on the cases of two forest management plans (FMPs). The selected units are parts of two larger forest complexes (Pohorje, Kočevsko), included in Natura 2000. We analyzed measures ensuring favorable condition of qualification species and habitat types and thus attaining protection objectives of the Natura 2000 areas. The measures enabling achieving protection objectives require adjusted economizing and thereby also certain limitations for forest owners.
Keywords: Natura 2000; biotska pestrost; biotska raznovrstnost; biodiversity; gozdovi; gozdni prostor; Slovenia; Slovenija